Spatial distribution of marine invasive species: environmental, demographic and vector drivers. Issue 7 (21st April 2014) - Clarke Murray, Cathryn; Gartner, Heidi; Gregr, Edward J.; Chan, Kai; Pakhomov, Evgeny; Therriault, Thomas W.
Abstract: Aim: The introduction of potentially invasive species remains a global threat to biodiversity and ecosystem services. The spatial distribution of introduced species can provide insight into present and historical vectors of invasion. Here, we aim to investigate the influence of environmental, demographic and vector variables on the spatial distribution of non‐indigenous species (NIS) in coastal marine ecosystems. Location: Coastal British Columbia, Canada. Methods: We used subtidal settlement plates to sample NIS richness at 81 sites. Spatial patterns for seventeen environmental, population, and vector variables were created using a Geographic Information System (GIS). We used multiple regression with model selection and spatial autocorrelation to define a statistical model that best explained the spatial distribution of NIS. Results: Four variables, salinity, human population density, port arrivals and marina propulsiveness (probability of boater travel from home marina), best explained the observed spatial distribution of subtidal NIS. Aquaculture, an original global introduction pathway, did not significantly explain the contemporary distribution of NIS. Results suggest that recreational boating is the most probable pathway of fouling NIS spread in this region, driving their current distribution. Spatial autocorrelation was significant for environmental, demographic, and aquaculture variables. However, marina propulsiveness and attractiveness were not autocorrelated, suggesting that boater behaviour varies on a finer scale. Main conclusions: A simple model using a combination of vector, demographic, and environmental characteristics can explain 43.6% of the variation in the spatial distribution of NIS. Our study provides further evidence that recreational boating is a significant pathway for the contemporary spread of NIS in marine environments. With projected increases in human population, we expect a continued rise in introduction rates and spread in this region and elsewhere in the world.